1986
DOI: 10.1083/jcb.102.5.1543
|View full text |Cite
|
Sign up to set email alerts
|

Secretory protein translocation in a yeast cell-free system can occur posttranslationally and requires ATP hydrolysis.

Abstract: Abstract. We describe an in vitro system with all components derived from the yeast Saccharomyces cerevisiae that can translocate a yeast secretory protein across microsomal membranes. In vitro transcribed prepro-a-factor mRNA served to program a membrane-depleted yeast translation system. Translocation and core glycosylation of prepro-a-factor were observed when yeast microsomal membranes were added during or after translation. A membrane potential is not required for translocation. However, ATP is required f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
166
0

Year Published

1987
1987
2000
2000

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 310 publications
(174 citation statements)
references
References 34 publications
8
166
0
Order By: Relevance
“…The precursors to a-factor and CPY, but not invertase, can be posttranslationally translocated across the membrane (Hansen et al, 1986;Rothblatt and Meyer, 1986;Waters and Blobel, 1986;Hansen and Walter, 1988). In this regard, we have previously demonstrated that the sec7l-1 and sec72-1 mutants accumulate ppCPY but not preinvertase .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The precursors to a-factor and CPY, but not invertase, can be posttranslationally translocated across the membrane (Hansen et al, 1986;Rothblatt and Meyer, 1986;Waters and Blobel, 1986;Hansen and Walter, 1988). In this regard, we have previously demonstrated that the sec7l-1 and sec72-1 mutants accumulate ppCPY but not preinvertase .…”
Section: Discussionmentioning
confidence: 99%
“…Some preproteins can be translocated across the membrane, in a posttranslational manner in yeast (Hansen et al, 1986;Rothblatt and Meyer, 1986;Waters and Blobel, 1986). Posttranslational translocation of the precursor to a-factor is mediated by cytoplasmic heatshock proteins (Chirico et al, 1988;Deshaies et al, 1988) and cytoplasmic Ydjlp, a DnaJ homologue (Caplan et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…A yeast translation extract programmed with prepro-ct-factor mRNA di- rects the synthesis of an intact precursor which can insert co-or posttranslationaUy into yeast microsomes and become core-glycosylated. The existence of a posttranslational reaction has allowed these investigators to demonstrate that protein translocation into the yeast ER is energy dependent (15,43,57). In addition, fractionation experiments suggest that the import reaction requires cytosolic components (58).…”
mentioning
confidence: 99%
“…The mechanism of protein permeation across the hydrophobic core of the ER membrane is not understood. Experiments with intermediates artificially blocked at various stages of membrane penetration suggest that this process is mediated by proteins, though they have yet to be identified by the existing assays (14).Recently, several groups have reconstituted protein translocation into the yeast ER in vitro (15,42,57). A yeast translation extract programmed with prepro-ct-factor mRNA di- rects the synthesis of an intact precursor which can insert co-or posttranslationaUy into yeast microsomes and become core-glycosylated.…”
mentioning
confidence: 99%
See 1 more Smart Citation